2012
DOI: 10.5539/ijbm.v7n10p156
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Professional Commitment of Chinese Project Management Professionals

Abstract: This paper reports the results of a questionnaire survey of Chinese PM Professionals' professional commitment (PC). It confirms the three PC dimensions of PM Career Pursuit Commitment, PM Reference Group Commitment, and PM Leisure Time Commitment. It reveals that the PM professionals' PC is positively correlated with their organizational positions, work experience, PM training, and their organizational commitment (OC). The PM professionals' PC and OC are both quite high, and their PC is even higher than their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Professional commitment refers to the kind of work commitment that focuses on the importance of a career in one’s life [ 42 ]. Professional commitment is an important indicator determining employees’ work behavior [ 43 ] and indicates an individual’s attitude toward the chosen profession [ 44 ]. The definition of professional commitment is equivalent to career commitment [ 45 ] or occupational commitment.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Professional commitment refers to the kind of work commitment that focuses on the importance of a career in one’s life [ 42 ]. Professional commitment is an important indicator determining employees’ work behavior [ 43 ] and indicates an individual’s attitude toward the chosen profession [ 44 ]. The definition of professional commitment is equivalent to career commitment [ 45 ] or occupational commitment.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Individuals need to manage their careers in order to prepare for future employment needs and remain efficient and relevant in their present employment Thus an individual's attitude toward career is described as career commitment. According to Morrow, (1993) as quoted by Wang;Shen (2012, p.156), "Career commitment is recognized as a form of work commitment that individuals have on a career facet". Also Commitment has been defined as a "force that binds an individual to a course of action", (MEYER; HERSCOVITCH, 2001).…”
Section: Relevance Of Thementioning
confidence: 99%
“…While in more details, the commitment of the profession contributes 33 percent and organizational commitment by 9 percent [11]. [22], [11] found that professional commitment correlates with organizational commitment to project management and teachers. Other studies found a negative relationship between professional commitment and turnover intentions.…”
Section: Introductionmentioning
confidence: 99%